Who Divorces Whom: Unilateral Divorce Legislation and the Educational Structure of Marriage - Geghetsik Afunts; Štepán Jurajda (Institute of Labor Economics (IZA), 2022)
There is evidence that the introduction of unilateral divorce legislation (UDL) starting in the late 1960s increased US divorce rates. We ask whether making divorce easier affected the educational structure of marriage. Based on marriage and divorce certificate data covering 1970-1988, we provide new evidence on the evolution of the educational structure of marriage inflows (newlyweds) and outflows (divorces), and estimate UDL difference-in-differences effects on both flows. While UDL did not contribute to rising homogamy (the tendency towards married partners having the same level of education), it did affect the educational structure of marriage: it made generally unstable hypogamous couples (women marrying less educated partners) less likely to divorce, and it made homogamous couples more stable than hypergamous ones (women marrying more educated partners).
Keywords: J12; 330; homogamy; unilateral divorce; marriage